1998
DOI: 10.1128/jvi.72.4.2881-2889.1998
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a CD2-Like Gene,8-DR, from African Swine Fever Virus Affects Viral Infection in Domestic Swine

Abstract: An African swine fever virus (ASFV) gene with similarity to the T-lymphocyte surface antigen CD2 has been found in the pathogenic African isolate Malawi Lil-20/1 (open reading frame [ORF] 8-DR) and a cell culture-adapted European virus, BA71V (ORF EP402R) and has been shown to be responsible for the hemadsorption phenomenon observed for ASFV-infected cells. The structural and functional similarities of the ASFV gene product to CD2, a cellular protein involved in cell-cell adhesion and T-cell-mediated immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
143
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(155 citation statements)
references
References 42 publications
(54 reference statements)
10
143
0
2
Order By: Relevance
“…For example, SPAAN (used in Vaxign) identified many spike glycoproteins from Human coronavirus as adhesins (Sachdeva et al, 2005) and the spike protein (S), a membrane component of Severe acute respiratory syndrome coronavirus (SARS-CoV), was identified to be critical for viral pathogenesis (Li et al, 2003b) and experimentally proven to be effective as a vaccine candidate (Bisht et al, 2004). The identified adhesion probability scores for EP402R (CD2v) (score 0.457) and EP153R (score 0.372) correlate with previous reports that have shown that these proteins are involved in ASFV hemadsorption (HA) in vitro (Borca et al, 1998(Borca et al, , 1994bGalindo et al, 2000;Neilan et al, 1999;Rodríguez et al, 1993;Ruiz-Gonzalvo et al, 1996). Adhesion probability scores were identified for B646L/p72 (score 0.25), CP204L/p30 (score 0.363), and E183L/p54 (score 0.566), all previously reported to be potential protective antigens (Argilaguet et al, 2012;Gómez-Puertas et al, 1998;Lokhandwala et al, 2016;Neilan et al, 2004).…”
Section: Discussionsupporting
confidence: 60%
“…For example, SPAAN (used in Vaxign) identified many spike glycoproteins from Human coronavirus as adhesins (Sachdeva et al, 2005) and the spike protein (S), a membrane component of Severe acute respiratory syndrome coronavirus (SARS-CoV), was identified to be critical for viral pathogenesis (Li et al, 2003b) and experimentally proven to be effective as a vaccine candidate (Bisht et al, 2004). The identified adhesion probability scores for EP402R (CD2v) (score 0.457) and EP153R (score 0.372) correlate with previous reports that have shown that these proteins are involved in ASFV hemadsorption (HA) in vitro (Borca et al, 1998(Borca et al, , 1994bGalindo et al, 2000;Neilan et al, 1999;Rodríguez et al, 1993;Ruiz-Gonzalvo et al, 1996). Adhesion probability scores were identified for B646L/p72 (score 0.25), CP204L/p30 (score 0.363), and E183L/p54 (score 0.566), all previously reported to be potential protective antigens (Argilaguet et al, 2012;Gómez-Puertas et al, 1998;Lokhandwala et al, 2016;Neilan et al, 2004).…”
Section: Discussionsupporting
confidence: 60%
“…In addition, this African swine fever virus protein has been shown to have an immunomodulatory role in vivo, by impairment of bystander lymphocyte functionality. 29 In the current study, we report the identification of a CD229 structural homologue encoded by the HCMV gene UL7. This viral product contains an Ig-like domain with significant amino acid identity with the CD229 N-terminal Ig-variable domain responsible for the homophilic interactions that result in T-cell signalling.…”
mentioning
confidence: 85%
“…Coggins (1968) and Vig ario et al (1974) reported that viruses lacking the ability to cause haemadsorption generally tend to be non-virulent or are of reduced virulence due to the deletion of the gene encoding the CD2v protein. This deletion delays the onset of viraemia and dissemination of viruses within infected pigs (Borca et al, 1998) and was previously linked to natural attenuation of ASFV. Nevertheless, other authors have found that certain nonhaemadsorbing ASFVs cause ASF (Leitão et al, 2001).…”
Section: Discussionmentioning
confidence: 88%